LINGUISTIC AND EXTRALINGUISTIC FACTORS FORMING THE CONCEPTUAL FIELD OF PARABLES - Solijonov Mukhammadjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The purpose of the article is to discuss and find out some features of linguistic and extra linguistic factors forming the conceptual field of parables. Moreover, the article illustrates the theoretical foundations of the study of culture through language.